On the origin of the Treponematoses: a phylogenetic approach - Harper, K; Ocampo, P; Steiner, B; George, R; Silverman, M; Bolotin, S; Pillay, A; Saunders, N; Armelagos, G (Public Library of Science, 2008)
Background: Since the first recorded epidemic of syphilis in 1495, controversy has surrounded the origins of the bacterium Treponema pallidum subsp. pallidum and its relationship to the pathogens responsible for other treponemal diseases: yaws, endemic syphilis, and pinta. Some researchers have argued that the syphilis-causing bacterium, or its progenitor, was brought from the New World to Europe by Christopher Columbus and his men, while others maintain that the treponematoses, including syphilis, have a much longer history on the European continent. Methodology/Principal findings: We applied phylogenetics to this problem, using data from 21 genetic regions examined in 26 geographically disparate strains of pathogenic Treponema. Of all the strains examined, the venereal syphilis-causing strains originated most recently and were more closely related to yaws-causing strains from South America than to other non-venereal strains. Old World yaws-causing strains occupied a basal position on the tree, indicating that they arose first in human history, and a simian strain of T. pallidum was found to be indistinguishable from them. Conclusions/Significance: Our results lend support to the Columbian theory of syphilis's origin while suggesting that the non-sexually transmitted subspecies arose earlier in the Old World. This study represents the first attempt to address the problem of the origin of syphilis using molecular genetics, as well as the first source of information regarding the genetic make-up of non-venereal strains from the Western hemisphere.